DEVELOPMENT AND EFFECTIVENESS OF TRI N-INTEGRATED DIGITAL LEARNING MEDIA TO ENHANCE EARLY LITERACY SKILLS IN ELEMENTARY SCHOOL STUDENTS - Eko Yulianto; Joko Sulianto; Achmad Buchori (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates the integration of Tri N values Niteni (observing), Niroke (imitating), and Nambahi (developing) into digital learning as an innovative approach to strengthen early literacy skills among elementary school students. Designed using the ADDIE development model, the digital learning media incorporated interactive text, images, animations, and narration to support multisensory literacy development. Data were collected through expert validation, student response questionnaires, and pre-test–post-test assessments conducted in experimental and control classes. The results indicate that the Tri N-based digital media significantly improved students’ early reading and writing abilities, as shown by an increase in the experimental group’s mean score from 70.1 to 85.7 and a moderate N-Gain of 57.76%. Statistical analysis further demonstrated a significant effect on reading (p = 0.000) and writing skills (p = 0.015). Despite positive learning outcomes, expert and student evaluations highlighted the need for improved navigation and instructional clarity. Overall, this study demonstrates that integrating Tri N values into digital learning environments offers a culturally grounded and pedagogically effective model for enhancing early literacy development.